ANALISIS PEMBERITAAN MEDIA ONLINE KAHABA.NET DENGAN BIMAKINI.COM TENTANG MASJID TERAPUNG ( Sebuah Framing Edisi Oktober 2017 – Januari 2018) - Irham Irham; Tasrif Tasrif; Junaidin Junaidin (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2022)
This study aims to understand and at the same time find out the difference between Kahaba.net and Bimakini.com's online media coverage of the floating mosque edition of October 2017-January 2018. Researchers reviewed the context of this study using a qualitative type of research with a framing analysis approach. Some of the data identified contained a number of different reports about the floating mosque, both online media kahaba.net and bimakini.net. The results of data analysis on the online media kabaha.net about the floating mosque can be seen from several parts, namely the news structure of the kahaba.net media contains fewer leads than the content of the news. From the Who Script Structure where more information is presented to the readers. And the Thematic structure Details in several paragraphs to emphasize a community who complains about irregularities. While the Rhetorical Structure Some of the choice of words by the online media Kahaba.net there are no words that are deliberately embellished to complete the content of the news, the use of idioms is the same. Only the use of captions on photos that describe an event that lacks detail makes the reader guess about the intent of the photo which makes the article less focused. Meanwhile, from the results of data analysis, the BimaKini.com online media framing about the Floating Mosque is as follows: